Short-Term Outcomes of Simultaneous Inguinal Hernia Repair at Laparoscopic Appendectomy in Children: Cohort Study - Vasily P. Gavrilyuk; Dmitry A. Severinov; Yulia A. Zubkova (Вопросы современной педиатрии, 2024)
Background. Nowadays, simultaneous techniques have been widely adopted in abdominal pediatric surgery as they allow to perform surgical interventions for several diseases at the same time. However, the safety of such interventions requires further studies. Objective. The aim of the study is to analyze the short-term outcomes of simultaneous hernia repair in laparoscopic appendectomy in children. Methods. The study included data from patients hospitalized with suspected acute appendicitis in 2022–2023. The study group included children operated for acute appendicitis and who had signs of patent processus vaginalis. Percutaneous internal ring suturing (PIRS) was performed in all cases. The control group (no indirect inguinal hernia was revealed) was formed by pairwise matching of patients by gender, age (± 1 year), and appendicitis type. The surgery time, the blood loss volume, the beginning of enteral feeding, and the presence of postoperative complications were analyzed. Results. The compared groups (13 individuals each) were comparable in gender (38% boys), age (median age about 10 years), and appendicitis type (catarrhal — 31%, phlegmonous — 38%, gangrenous — 31%), and white cell count at admission, presence of serous exudate and omentum changes revealed during surgery. The beginning of enteral feeding, the stool, as well as total duration of hospital stay after surgery did not differ in two groups. Moreover, both groups were comparable in terms of surgery duration, intraoperative blood loss volume, pain syndrome severity. No pyo-inflammatory complications of abdominal cavity or postoperative wounds were revealed during the hospital stay. Conclusion. Simultaneous hernia repair via PIRS method is effective and safe method of surgical management of pediatric patients with combination of acute appendicitis and inguinal hernia.